Dysregulation of Chemokine/Chemokine Receptor Axes and NK Cell Tissue Localization during Diseases - Bernardini, Giovanni; Antonangeli, Fabrizio; Bonanni, Valentina; Santoni, Angela (Frontiers in Immunology, 2016)
ABSTRACT Chemokines are small chemotactic molecules that play key roles in physiological and pathological conditions. Upon signaling via their specific receptors, chemokines regulate tissue mobilization and trafficking of a wide array of immune cells, including NK cells. Current research is focused in analyzing changes of chemokine/chemokine receptor expression during various diseases to interfere with pathological trafficking of cells, or to recruit selected cell types to specific tissues. NK cells are a heterogeneous lymphocyte population comprising several subsets endowed with distinct functional properties and mainly representing distinct stages of a linear development process. Because of their different functional potential, the type of subset that accumulates in a tissue drives the final outcome of NK cell-regulated immune response, leading to either protection or pathology. Correspondingly, chemokine receptors including CXCR4, CXCR3 and CX3CR1 are differentially expressed by NK cell subsets and their expression levels can be modulated during NK cell activation. This review will at first summarize the current knowledge on the contribution of chemokines to the localization and generation of NK cell subsets in homeostasis. How an inappropriate chemotactic response can lead to pathology and how chemokine targeting can therapeutically affect tissue recruitment/localization of distinct NK cell subsets will also be discussed.